Promises and challenges of a decentralized CAR T-cell manufacturing model - Shah, Manan; Krull, Ashley; Odonnell, Lynn; de Lima, Marcos J.; Bezerra, Evandro (Frontiers in Transplantation, 2023)
Autologous chimeric antigen receptor-modified T-cell (CAR T) products have demonstrated unprecedent efficacy in treating many relapsed/refractory B-cell and plasma cell malignancies, leading to multiple commercial products now in routine clinical use. These positive responses to CAR T therapy have spurred biotech and big pharma companies to evaluate innovative production methods to increase patient access while maintaining adequate quality control and profitability.Autologous cellular therapies are, by definition, manufactured as single patient batches, and demand has soared for manufacturing facilities compliant with current Good Manufacturing Practice (cGMP) regulations. The use of a centralized production model is straining finite resources even in developed countries in North America and the European Union, and patient access is not feasible for most of the developing world. The idea of having a more uniform